Antioxidant glutathione inhibits inflammation in synovial fibroblasts via PTEN/PI3K/AKT pathway: An in vitro study - Wen Ting Hao,; Lu Huang,; Wei Pan,; Yi Le Ren, (Archives of Rheumatology, 2022)
Objectives: In this study, we aimed to investigate whether glutathione (GSH) could decrease the secretion of reactive oxygen species (ROS), reduce inflammation, and modulate the phosphatase and tensin homolog deleted on chromosome 10/phosphatidylinositol 3-kinase/AKT (PTEN/PI3K/AKT) in synovial fibroblasts (SFs). Patients and methods: A total of 30 DBA/1J female mice were used in this study. The release of ROS in MH7A cells was examined using a ROS assay kit. The effects of GSH on the messenger ribonucleic acid (mRNA) expression and protein levels of inflammatory cytokines were determined via reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and enzyme-linked immunosorbent assay (ELISA) in mouse SFs and MH7A cells, respectively. The PTEN/PI3K/AKT pathway was investigated via Western blotting. The effects of buthionine-sulfoximine (BSO), as an inhibitor of GSH, on these molecules were examined. Results: The ROS were decreased after GSH treatment, and the mRNA levels of tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1β, IL-6, matrix metalloproteinase (MMP)-1, MMP-3, were also significantly inhibited after GSH stimulation. However, the IL-10 levels were enhanced, and GSH increased the expression of PTEN. The GSH suppressed the activation of phosphorylated (p)-PI3K and p-AKT. The supplementation of the BSO restored the activation of PI3K/AKT pathway with a high production of ROS. The levels of TNF-α, IL-1β and IL-6 were also elevated, when the BSO was added. Conclusion: These findings suggest that GSH can act as an inflammatory suppressor by downregulating the PTEN/PI3K/AKT pathway in MH7A cells. These data indicated a novel function of GSH for improving the inflammation of RA SFs and may help to alleviate the pathological process of RA.